Stock Returns on Customer Satisfaction Do Beat the Market: Gauging the Effect of a Marketing Intangible. (September 2016) - Fornell, Claes; Morgeson, Forrest V.; Hult, G. Tomas M.
A debate about whether firms with superior customer satisfaction earn superior stock returns has been persistent in the literature. Using 15 years of audited returns, the authors find convincing empirical evidence that stock returns on customer satisfaction do beat the market. The recorded cumulative returns were 518% over the years studied (2000–2014), compared with a 31% increase for the S&P 500. Similar results using back-tested instead of real returns were found in the United Kingdom. The effect of customer satisfaction on stock price is, at least in part, channeled through earnings surprises. Consistent with theory, customer satisfaction has an effect on earnings themselves. In addition, the authors examine the effect of stock returns from earnings on stock returns from customer satisfaction. If earnings returns are included among the risk factors in the asset pricing model, the earnings variable partially mitigates the returns on customer satisfaction. Because of the long time series, it is also possible to examine time periods when customer satisfaction returns were below market. The reversal of the general trend largely resulted from short-term market idiosyncrasies with little or no support from fundamentals. Such irregularities have been infrequent and eventually self-correcting. The authors provide reasons why irregularities may occur from time to time.